Jiwa Kewirausahaan dan Strategi Keberhasilan dalam Penjualan - Sri Indrahti; Siti Maziyah; Alamsyah Alamsyah (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
Sales strategy in entrepreneurship activities has an important role in the success of the business. It takes persistence to create mutual trust between the seller and the buyer. Some of the efforts made by sellers who are engaged in the MSME sector in Semarang, among others, maintain quality, have standard prices according to the market and conduct healthy competition between sellers with the same or various types of business.